Advancing the Green Hospitality Marketing Landscape: A Systematic Review and Integrated Conceptual Framework (2020–2025) - Muxisddin O’g’li , Xusniddinov Yorqinjon; Susanto, Eko (Journal of Consumer Studies and Applied Marketing, 2025)
This study conducts a systematic literature review (SLR) of green marketing research in the hospitality industry from 2020 to 2025—a period characterized by post-pandemic recovery and intensified sustainability imperatives. Following the PRISMA 2020 guidelines, 82 peer-reviewed Scopus-indexed articles were analyzed using a combination of bibliometric mapping and thematic synthesis. The review reveals a sharp increase in scholarly output, led by contributions from Indonesia and China, indicating a geographical shift of sustainability discourse toward emerging economies. Thematic clustering identifies three dominant research streams: (1) guest psychological mechanisms, (2) strategic green branding and innovation, and (3) digital transformation in operationalizing green practices. Theoretically, the field remains anchored in the Theory of Planned Behavior (TPB) and the Stimulus–Organism–Response (SOR) model, with growing integration of digital stimuli (e.g., Augmented Reality, Big Data) and mediators such as green trust and authenticity. Key research gaps include the persistent intention–behavior divide and the escalating risk of greenwashing skepticism. To address these issues, this study introduces the Integrated Green Hospitality Marketing Framework (IGHMF), which links organizational innovation with consumer psychology. The review offers a structured research agenda emphasizing longitudinal and cross-cultural studies to advance the transition from symbolic eco-labeling toward authentic, behavior-driven sustainability in hospitality marketing.